KONSEP PENDIDIKAN AKHLAK MENURUT AL-GHAZALI DAN IBN MISKAWAIH: SEBUAH KAJIAN PERBANDINGAN - Musleh (Educational Research Center, 2025)
This article explores a comparative study of the concept of moral education as formulated by two prominent Islamic thinkers, Al-Ghazali (1058–1111) and Ibn Miskawaih (932–1030). Although originating from distinct intellectual traditions—Al-Ghazali with his strong theological-mystical orientation and Ibn Miskawaih with his philosophical-ethical approach—both figures made significant contributions to the development of moral education within the Islamic intellectual heritage. The objective of this study is to analyze the similarities and differences in their perspectives and to highlight their relevance to contemporary educational discourse. Methodologically, this research employs a qualitative approach through library-based studies, examining classical works such as Ihya’ Ulum al-Din by Al-Ghazali and Tahdhib al-Akhlaq by Ibn Miskawaih, alongside secondary sources that provide scholarly interpretations of their ideas. The findings reveal that both thinkers emphasize the cultivation of virtue and the purification of the soul as the primary goals of education, yet they differ in their epistemological foundations and pedagogical strategies. Al-Ghazali emphasizes spiritual refinement and the integration of religious devotion, whereas Ibn Miskawaih stresses rational balance and ethical habituation. Theoretically, this study contributes to the ongoing discourse on Islamic moral philosophy by bridging theological and philosophical perspectives. Practically, it offers insights for contemporary educators on integrating ethical and spiritual dimensions into curriculum design, particularly in addressing the challenges of moral decline in modern society. Thus, this comparative framework not only enriches Islamic educational thought but also provides universal lessons applicable across cultural and religious contexts.